LEGALITAS PERKAWINAN KEMBALI EKSISTING PADA AKTA CERAI SUAMI ISTRI BERAGAMA KRISTEN - Waluyo Adi, Emmanuel Ariananto (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
According to state law, marriage and divorce are legal as long as they do not violate the provisions of the Marriage Law and related regulations, whereas Christianity prohibits divorce and remarriage based on the Bible. Divorce in the domestic relationship between husband and wife is legally permissible as long as it follows the provisions in the Marriage Law, Implementing Regulations, as wThe research aims from the Church where the marriage is solemnized so that the divorce certificate and remarriage certificate are valid according to national law outside of religious law. Research This study looks at the comparison of the law governing the divorce of married couples in Indonesia with Christian religious law and the conditions recognized by law for divorced Christian couples who will remarry. The research aims to find out the legal regulations regarding divorce between husband and wife in Indonesia and the mechanism for divorced Christian couples to remarry. Writing Method, the method used in this writing is a normative juridical approach. reviewing legal procedures based on legal materials carried out by collecting legal materials through literature studies related to the Legal Position of Divorce Deeds of Christian Husbands and Wives in the Event of Remarriage. The research concludes that it is not explained in the law that divorce is legal according to each religion, it only explains the validity of marriage so that in Christian marriages there is a mechanism for remarriage.